Numerical simulation of sediment transport in open channel - 326737 Chin, Yao Sheng (Skudai : Universiti Teknologi Malaysia, 2006)
Project Paper (Sarjana Muda Kejuruteraan Awam) - Universiti Teknologi Malaysia, 2006